Pemahaman Teologi Kristen dalam Meningkatkan Efektivitas Pembelajaran Pendidikan Agama Kristen - Ayu Santriana Retebana; Ririn Andini Tainmeta (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the role of understanding Christian theology in improving the quality of Christian Religious Education (CRE) learning. The focus of the study is how theological foundations can shape students’ character, morals, and spiritual development, as well as how teachers’ instructional strategies can support the achievement of these learning outcomes optimally and sustainably. The method used is a qualitative literature review, analyzing various relevant books and journal articles related to CRE, teaching approaches, and the integration of faith values into the educational curriculum. The findings indicate that mastery of Christian theology serves as an essential foundation in learning, as it enables students to understand their faith deeply while also internalizing Christian principles in their daily lives. In addition, interactive, contextual, and participatory learning methods have been shown to increase student engagement and motivation in the learning process. The role of the teacher as a moral and spiritual role model is also a key factor in strengthening the internalization of these values. Thus, an understanding of Christian theology not only supports cognitive aspects but also contributes to shaping students’ character and ethical behavior, making CRE learning transformational and holistic.